??-Statistical boundedness on time scales - Altin, Yavuz; Er, Busra Nur; Yilmaz, Emrah (Taylor & Francis Inc, 2021)
In this study, we examine the notion of Delta(lambda)-statistical boundedness on an arbitrary time scale. Moreover, some inclusion relations are obtained.
Keywords: Statistical convergence; sequence spaces; time scales